EL CONTRATO COMO ORIGEN DE LAS SOCIEDADES MERCANTILES, EN EL DERECHO ESPAÑOL - COMPARACIÓN CON EL DERECHO PERUANO - Garcia Pita, José Luis (Revista de Derecho, 2019)
The obvious and undeniable peculiarities that distinguish a company’s foundation actfrom the traditional bilateral contract have led to the apparition of different theoriesabout the legal nature of such act at various times and places. Many of them have incommon the denial of its contractual character. However, a more careful analysis allowsto unequivocally assert that character, and thus the full validity of the traditional conceptof “company contract”, its plurilateral nature (“two or more people”) and its radial structure(“who bind themselves to put jointly”). An indeed exceptional case —and yet, equallycontractual in nature— may be found in the very special instance of the so-called successivefoundation of companies.
Keywords: institutional theory of companies; organizatory act; complex act; company contract; succesive foundation of companies